3D Manipulation of Magnetic Liquid Metals. (12th July 2020) - Zhou, Wenqing; Liang, Qingxuan; Chen, Tianning
Abstract : Herein, a new method for steering liquid metals (LMs) using only a magnetic field in open 3D space is proposed. The magnetic LM is composed of the alloy Galinstan and iron particles. The 3D horizontal and vertical manipulation of a magnetic LM can be realized via an external magnetic field. The magnetically actuated LM is not only manipulated on various complex pathways in the horizontal plane, but also vertically in 3D space without the use of electrolytes and electrodes. As a proof‐of‐principle, an intelligent delivery vehicle that can avoid obstacles and traps horizontally and overcome gravity vertically to offload a cargo is designed and implemented successfully. Furthermore, a biomimetic soft robotics that can realize both in‐plane and out‐of‐plane locomotion is demonstrated using only magnetic field. The novel 3D motion of the demonstrated system facilitates the development of practical LM‐based smart structures and devices. Abstract : A novel manipulating method for liquid metal (LM) in open 3D space using only a magnetic field, for the first time, is proposed experimentally. As a proof‐of‐concept, an intelligent delivery vehicle and a biomimetic soft robotics are demonstrated to validate the extraordinary steering performance that can facilitate the development of practical LM‐based smart structures and devices.